Role of Micronucleus-Limited DNA in Programmed Deletion of mse2.9 during Macronuclear Development of Tetrahymena thermophila - Fillingham, Jeffrey S. (American Society for Microbiology, 2004)
Extensive programmed DNA rearrangements occur during the development of the somatic macronucleus from the germ line micronucleus in the sexual cycle of the ciliated protozoan Tetrahymena thermophila. Using an in vivo processing assay, we analyzed the role of micronucleus-limited DNA during the programmed deletion of mse2.9, an internal eliminated sequence (IES). We identified a 200-bp region within mse2.9 that contains an important cis-acting element which is required for the targeting of efficient programmed deletion. Our results, obtained with a series of mse2.9-based chimeric IESs, led us to suggest that the cis-acting elements in both micronucleus-limited and macronucleus-retained flanking DNAs stimulate programmed deletion to different degrees depending on the particular eliminated sequence. The mse2.9 IES is situated within the second intron of the micronuclear locus of the ARP1 gene. We show that the expression of ARP1 is not essential for the growth of Tetrahymena. Our results also suggest that mse2.9 is not subject to epigenetic regulation of DNA deletion, placing possible constraints on the scan RNA model of IES excision.